The usability of bioelectrical impedance analysis in overweight and obese children - Krzywulski, Aleksander; Jurkowska, Urszula; Bugla, Błażej (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Obesity, a chronic recurrent disease related to excessive fat tissue accumulation that leads to numerous health problems, is a significant public health concern. Accurate methods to estimate body composition are crucial for diagnosis and treatment of obesity. The purpose of this paper was to evaluate whether bioelectrical impedance analysis (BIA) is a sufficiently reliable method for assessing body composition (BC) in obese children for daily use in clinical practice. Inclusion criteria were English-written studies published between 2018 and February 2024, available in PubMed database, and relating to BIA and its use in pediatric obesity. The review included 31 studies showing that BIA has advantages over body mass index, but exhibits bias in comparison to dual energy X-ray absorptiometry, which can be reduced using multifrequency octopolar devices. BIA-derived measurements are associated with obesity’s biochemical and clinical markers. BIA is currently the most easily accessible and sufficiently accurate method for measuring BC.